Effect of switching pedal rate model on slow component of oxygen uptake during heavy-cycle exercise - Migita, T.; Hirakoba, K. (Biology of Sport, 2007)
We examined the effect of a change in the muscle fiber recruitment patterns on the occurrence of the VO2 slow component (VO2SC) using both a previously employed exercise model for maintaining a given pedal rate (60 rpm: 60con or 110 rpm:110con) throughout constant-load exercise and a newly designed exercise model for switching the pedal rate at the halfway point (60—110 rpm:60—>110swi or 110-»60 rpm:110—>60swi) during constant-metabolic demand cycling exercise. Seven healthy male volunteers [mean ± SD: age 24±2 years, body mass 64.8±7.5 kg] performed four square-wave transitions at work rates calculated from each relationship between the oxygen uptake and the work rate obtained in two incremental cycling tests with 60 rpm and 110 rpm. The work rates were set to require a VO2 at the ventilatory threshold (VT) plus a VO2 equal to 50% of the difference between the VT and the peak VO2 (50%Delta). Both pulmonary gas exchange parameters and surface electromyogram (EMG) were measured during all transition exercises. VO2 above rest (DeltaVO2) divided by the total mechanical power Output (Wtot = external + internal power Outputs) (DeltaVO2/Wtot), which was estimated as an index for the oxygen cost per unit of all work accomplished in 60—»110swi and 110—>60swi, showed either a decrease or an increase concomitant with the switching pedal rates, respectively. Similarly, the integrated EMG (iEMG) after the halfway point of the exercise tests tended to decrease for 60—»llOswi and increase for 110—»60swi, respectively. From the results of this study (DeltaVO2/Wtot and iEMG responses), it is inferred that the exercise model designed in this study may induce a change in the muscle fiber recruitment pattern from the halfway point during constant-metabolic demand exercise. However, no differences were observed in the amplitude of the VO2SC among the four trials, thus indicating that a change in the muscle fiber recruitment pattern is therefore not closely related to the appearance of VO2SC during constant-metabolic demand cycling exercise. Therefore, we believe that some other factors exist in the exercising muscle which is responsible for the induction of VO2SC.